Fighting Asian Soybean Rust - Langenbach, Caspar; Campe, Ruth; Beyer, Sebastian F.; Mueller, André N.; Conrath, Uwe (Frontiers in Plant Science, 2016)
Phakopsora pachyrhizi is a biotrophic fungus provoking Asian soybean rust (SBR) disease. SBR poses a major threat to global soybean production. Though several resistance genes provided soybean immunity to certain P. pachyrhizi races, the pathogen swiftly overcame this resistance. Therefore, fungicides are the only current means to control SBR. However, insensitivity to fungicides is soaring in P. pachyrhizi and, therefore, alternative measures are needed for SBR control. In this article, we discuss the different approaches for fighting SBR and their potential, disadvantages, and advantages over other measures. These encompass conventional breeding for SBR resistance, transgenic approaches, exploitation of transcription factors, secondary metabolites, and antimicrobial peptides, RNAi/HIGS, and biocontrol strategies. It seems that an integrating approach exploiting different measures is likely to provide the best possible means for the effective control of SBR.